Using Multitarget Molecular Docking to Examine the Antiviral Potential of Clerodendrum Phlomidis against Measles - Sampriya Raj; Samiksha Bhor (International Journal of Molecular Biotechnological Research, 2023)
Objective: Measles, a viral disease caused by a member of the Paramyxoviridae virus family, is highly contagious and characterized by a respiratory illness and a maculopapular rash on the skin. Children are the main victims of the illness. In the context of drug development, this study investigates the efficacy of phytocompounds derived from Clerodendrum phlomidis against the target protein of the measles virus. Methods: The 7SKS protein was retrieved from the Protein Data Bank (PDB) database. Molecular docking studies were conducted systematically using PyRx and BIOVIA Discovery Studio Visualizer to assess the binding affinities of phytocompounds to the target protein. To evaluate the pharmacological properties of the phytocompounds, Swiss-ADME and ADMET lab were employed. Results: The docking results indicate that among the phytocompounds tested, Pectolinarin, beta-sitosterol, Clerodendrin A, Clerodin, Clerosterol, Daucosterol, Scutellarein, and Sterol exhibited the highest binding affinities to the target protein. However, based on the ADMET profile and drug-likeness prediction analysis, Clerodin and Scutellarein were found to have drug-like properties among the eight compounds evaluated. Conclusions: The results of this study indicate that Clerodin and Scutellarein possess specific binding affinity and therefore may be effective against the matrix protein. As such, these phytocompounds hold potential for use in therapeutic strategies against measles disease
Keywords: 7SKS protein; ADME; Clerodendrum phlomidis; Measles disease; Paramyxoviridae; molecular docking; phytocompounds